Development of a Simple Integrative Carbon Nanomaterial Microextraction Method with GC-MS for Assessing Pesticide Residues in Apples - Eduard F. Valenzuela; Leiliane C. André; Helvecio C. Menezes; Zenilda L. Cardeal (Journal of Chemistry)
The present study describes an efficient analytical method for analyzing apple pesticide residues. This novel approach employs ultrasound-assisted cleaning (UAC), solid-phase microextraction (SPME), and gas chromatography/mass spectrometry (GC-MS). A fiber coating with carbon nanomaterials (CNMs) was used for the extraction process. The methodology underwent extraction process optimization and analytical method validation. Moreover, its applicability for detecting pesticides in apples was evaluated. The validation showed satisfactory results with linearity coefficients greater than 0.99 (R2 > 0.99) and linear working ranges from 0.5 ng·g−1 to 300.0 ng·g−1. The limits of detection and quantification (LODs and LOQs) ranged from 0.1 ng·g−1 to 0.3 ng·g−1 and from 0.5 ng·g−1 to 0.7 ng·g−1, respectively. The calculated recovery values ranged from 79% to 98%. The precision presented a relative standard deviation (RSD) lower than 14%. The validated method was applied to apple samples acquired from different markets and fruit stands in Belo Horizonte, Minas Gerais, Brazil. Organophosphate pesticides typically used in Brazilian apple production areas were detected in some samples. This study demonstrates the utility of UAC and CNM microextraction as an effective and highly efficient approach for analyzing pesticides in apples.